2015
DOI: 10.1002/er.3385
|View full text |Cite
|
Sign up to set email alerts
|

Cathode candidates for zinc-based thermal-electrochemical energy storage

Abstract: SUMMARYAn electrochemical cell utilizing a molten salt eutectic electrolyte (ZnCl 2 -KCl) is investigated as a new low-cost energy storage technology. Using Zn as the anode, a broad range of candidate cathode materials (Al, Ag, Bi, C, Cu, a Ni alloy, Sn, and Pb) are characterized by open-circuit potential, chronoamperometry, and electrochemical impedance spectroscopy methods. Cells employing the molten metal cathodes Sn, Bi, and Pb deliver markedly high current densities independent of their standard reduction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…The above analysis could also explain the >100% coulombic efficiencies observed in the first cycles, where Bi(l) may irreversibly accept small amounts of reduced Zn, although elemental analysis did not indicate the presence of Zn in the Bi electrode. Also possible is the dissolution of electrodes into the molten salt electrolyte as solvated, reduced metal; however, in this work and previous work we observed negligible self‐discharge, energy‐dispersive X‐ray (EDX), or differential scanning calorimetry (DSC) data that would suggest significant metal dissolution had occurred . Insoluble species may be deposited as a thin solid‐electrolyte interphase (SEI) at one or both of the electrodes from a small uptake of ambient O 2 or H 2 O during testing (e.g., in the form of ZnO or oxychlorides).…”
Section: Resultsmentioning
confidence: 52%
See 3 more Smart Citations
“…The above analysis could also explain the >100% coulombic efficiencies observed in the first cycles, where Bi(l) may irreversibly accept small amounts of reduced Zn, although elemental analysis did not indicate the presence of Zn in the Bi electrode. Also possible is the dissolution of electrodes into the molten salt electrolyte as solvated, reduced metal; however, in this work and previous work we observed negligible self‐discharge, energy‐dispersive X‐ray (EDX), or differential scanning calorimetry (DSC) data that would suggest significant metal dissolution had occurred . Insoluble species may be deposited as a thin solid‐electrolyte interphase (SEI) at one or both of the electrodes from a small uptake of ambient O 2 or H 2 O during testing (e.g., in the form of ZnO or oxychlorides).…”
Section: Resultsmentioning
confidence: 52%
“…Thus, Sn ( ρ m = 7.0 g cm −3 ) was selected as a compatible host anode metal . Ultimately, Bi was selected as a cathode candidate because it has the largest reduction potential relative to Zn and the largest predicted power density as a cathode in our previous studies . These results led us to develop the all‐molten Sn(Zn)|ZnCl 2 :KCl|Bi cell.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Fernández‐Olmo et al concluded that for the semiconductor manufacturing, it is required to use high‐purity chemical products, to avoid short circuits as a consequence of some deformation occurring in the electronic wafers, resulting in performance loss. In addition, it has been determined that the impurities contained in the materials used in the manufacturing process of the batteries can affect their performance …”
Section: Introductionmentioning
confidence: 99%